HUBUNGAN PERSEPSI SISWA TENTANG PENGGUNAAN STRATEGI PEMBELAJARAN DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH DI MA DARUL HUDA PUSAT MANDALAWANGI PANDEGLANG - Mohammad Nasrudin (QATHRUNÂ, 2019)
The purpose of this study is to analyze and test hypotheses about the relationship of students' perceptions about the use of learning strategies and learning motivation with the results of learning Fiqh. The benefits of this study provide a treasure trove of student perceptions about the use of learning strategies and learning motivation to do with student learning outcomes. The method used in this research is descriptive method with correlational techniques. The population of this study were all students of Madrasa Aliyah Darul Huda Mandalawangi Pandeglang Center in the even semester of the 2019-2020 academic year, totaling 281 students. The sample consisted of all XI classes, namely 81 students. The sampling technique used was purposive sampling. Data analysis used multiple correlation test and multiple regression test. The results of this study are: There is a positive and significant relationship between X1 and Y of 0.936, meaning that it is classified as very strong, There is a positive and significant relationship between X2 and Y of 0.479, meaning that it is classified as quite strong, There is a positive and significant relationship between X1, X2 with Y of 0.95, meaning that it is classified as very strong. The conclusions of the results of this study are useful for improving student learning outcomes with students' perceptions about the use of learning strategies and motivation to learn.